KESADARAN ESTETIS MENURUT HANS-GEORG GADAMER (1990-2002) - -, Sunarto (Harmonia: Journal of Arts Research and Education, 2011)
Hans-Georg Gadamer (1900-2002) adalah seorang filsuf dalam bidang hermeneutika yang sangat terkenal. Menjelang pensiunnya tahun 1960, kariernya menanjak dengan diterbitkan bukunya, Wahrheit und Method atau Truth and Method. Dalam bukunya Gadamer memberikan pemahaman pada tingkatan ontologis bukan metodologis. Di sini Gadamer ingin mencapai kebenaran tidak lewat metode melainkan dengan dialektika. Alasannya, dengan dialektika mengandaikan suatu kebebasan dalam mengajukan berbagai pertanyaan dibanding dalam proses metodis. Berangkat dari hal tersebut Gadamer merambah ke persoalan estetik (seni). Gadamer mengatakan bahwa dalam estetis ditemukan kebenaran, tetapi bukan kebenaran melalui metodis (penalaran) melainkan kebenaran yang menurut faktanya Ã¢â‚¬Å“berlainan dengan kebenaran metodisÃ¢â‚¬Â. Gadamer juga mencetuskan tentang konsep Ã¢â‚¬Å“permainanÃ¢â‚¬Â.Ã‚Â Hans-Georg Gadamer (1990-2002) is a famous philosopher in Hermeneutics. During his retirement in 1960, his career escalated by the publishing of his book, Wahrheit und Method or Truth and Method. In his book, Gadamer gives an ontological and not a methodological understanding. In this case, Gadamer wanted to achieve the truth, not through method but by dialectics. The reason is that the dialectics enables people to imagine freedom in proposing various questions rather than those in methodical process. Starting from these things, Gadamer explored more on aesthetic subjects (arts). Gadamer said that in aesthetics, he found truth, but not the truth through methodical process (reasoning) but the truth based on its facts, Ã¢â‚¬Å“different from its methodical truth.Ã¢â‚¬Â Gadamer also proposed a concept of Ã¢â‚¬Å“games.Ã¢â‚¬Â